mTOR Promotes Antiviral Humoral Immunity by Differentially Regulating CD4 Helper T Cell and B Cell Responses - Ye, Lilin (J Virol, 2017)
mTOR has important roles in regulation of both innate and adaptive immunity, but whether and how mTOR modulates humoral immune responses have yet to be fully understood. To address this issue, we examined the effects of rapamycin, a specific inhibitor of mTOR, on B cell and CD4 T cell responses during acute infection with lymphocytic choriomeningitis virus. Rapamycin treatment resulted in suppression of virus-specific B cell responses by inhibiting proliferation of germinal center (GC) B cells. In contrast, the number of memory CD4 T cells was increased in rapamycin-treated mice. However, the drug treatment caused a striking bias of CD4 T cell differentiation into Th1 cells and substantially impaired formation of follicular helper T (Tfh) cells, which are essential for humoral immunity. Further experiments in which mTOR signaling was modulated by RNA interference (RNAi) revealed that B cells were the primary target cells of rapamycin for the impaired humoral immunity and that reduced Tfh formation in rapamycin-treated mice was due to lower GC B cell responses that are essential for Tfh generation. Additionally, we found that rapamycin had minimal effects on B cell responses activated by lipopolysaccharide (LPS), which stimulates B cells in an antigen-independent manner, suggesting that rapamycin specifically inhibits B cell responses induced by B cell receptor stimulation with antigen. Together, these findings demonstrate that mTOR signals play an essential role in antigen-specific humoral immune responses by differentially regulating B cell and CD4 T cell responses during acute viral infection and that rapamycin treatment alters the interplay of immune cell subsets involved in antiviral humoral immunity. IMPORTANCE mTOR is a serine/threonine kinase involved in a variety of cellular activities. Although its specific inhibitor, rapamycin, is currently used as an immunosuppressive drug in transplant patients, it has been reported that rapamycin can also stimulate pathogen-specific cellular immunity in certain circumstances. However, whether and how mTOR regulates humoral immunity are not well understood. Here we found that rapamycin treatment predominantly inhibited GC B cell responses during viral infection and that this led to biased helper CD4 T cell differentiation as well as impaired antibody responses. These findings suggest that inhibition of B cell responses by rapamycin may play an important role in regulation of allograft-specific antibody responses to prevent organ rejection in transplant recipients. Our results also show that consideration of antibody responses is required in cases where rapamycin is used to stimulate vaccine-induced immunity.